Functional Outcome and Complications Following PHILOS Plate Fixation inProximal Humeral Fractures - Hussain, Shafqat; Amin, Muhammad Suhail; Hussain, Mehmood; Munir, Ali Arslan; Jabeen, Sundus; Iqbal, Muhammad Noman (Pakistan Armed Forces Medical Journal, 2024)
Objective: The purpose of this study is to assess the functional outcome following plate fixation with the Proximal HumeralInternal Locking System and to study complications associated with it.Study design: Prospective longitudinal study.Place and duration of study: Department of Orthopedic Surgery, Combined Military Hospital, Rawalpindi Pakistan, for 14months from 01 Sep 2021 – 31 Oct 2022.Methodology: A total of 75 patients participated in this study. Patients included in the study were aged 18 years or above withdisplaced proximal Humeral fractures. Patients were selected from in-patient department. They were explained the purpose ofthe study and those who consented to participate in the study were enrolled through a written consent form. ProximalHumeral Interlocking system was applied under general anesthesia. Follow up at 01 months, 03 months and 06 months wascarried out for functional outcome & complications if any.Results: A total of 75 patients were registered in this study. Average age of cohort was 42.05±15.83 years with 46 males and 29females. At 06 months the mean Constant score of the cohort was 58.96±6.44 and mean ASES score was 60.15±8.08. Mostcommon complication seen was superficial wound site infection with a frequency of 6(8%) that was resolved with dressing.Conclusion: Functional outcome of Proximal Humeral Fractures managed with Interlocking system is very effective, though itdeclines with age.Early mobilization of shoulder joint is achievable without compromising union of fracture segments.